Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1515/sjs-2016-0003
|View full text |Cite
|
Sign up to set email alerts
|

The Closeness of Young Adults’ Relationships with Their Parents

Abstract: Abstracts How close are the relationships between young adults and their parents today? Which factors account for closer or less close relationships between the generations? The theoretical model considers opportunity, need, family and cultural-contextual structures. The empirical analyses draw on the Swiss TREE survey (“Transitions from Education to Employment”). They reveal remarkably close ties between the generations. However, we also find a number of strains, such as the separation of parents and une… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 49 publications
0
19
0
4
Order By: Relevance
“…Across studies, these findings are in line with the view that females are more connected to family than males (Aquilino, 2006; Crocetti & Meeus, 2014; Fuligni & Pedersen, 2002). Moreover, our results revealed that female emerging adults were found to be closer to mothers than to fathers (Bertogg & Szydlik, 2016; Tsai et al, 2013) and to report greater levels of maternal secure attachment than their male counterparts did (Ponti & Smorti, 2019). In addition, Yanir and Guttmann (2011) demonstrated that mothers' rankings of connectedness to their children and of their children's accomplishment of emerging adulthood tasks were higher than fathers' rankings.…”
Section: Family Dynamics During Emerging Adulthood: What We Already Knowmentioning
confidence: 58%
See 2 more Smart Citations
“…Across studies, these findings are in line with the view that females are more connected to family than males (Aquilino, 2006; Crocetti & Meeus, 2014; Fuligni & Pedersen, 2002). Moreover, our results revealed that female emerging adults were found to be closer to mothers than to fathers (Bertogg & Szydlik, 2016; Tsai et al, 2013) and to report greater levels of maternal secure attachment than their male counterparts did (Ponti & Smorti, 2019). In addition, Yanir and Guttmann (2011) demonstrated that mothers' rankings of connectedness to their children and of their children's accomplishment of emerging adulthood tasks were higher than fathers' rankings.…”
Section: Family Dynamics During Emerging Adulthood: What We Already Knowmentioning
confidence: 58%
“…Discrepancies in the reports provided by parents and their children regarding family dynamics were identified. On the one hand, parents were found to perceive relationships with their children as being closer than the children did (Bertogg & Szydlik, 2016), reporting higher levels of family cohesion, communication (Givertz & Segrin, 2014), and parental knowledge than children did (Padilla‐Walker et al, 2008). Parents also reported less use of permissive and authoritarian parenting and greater levels of authoritative parenting than offspring did (Givertz & Segrin, 2014).…”
Section: Family Dynamics During Emerging Adulthood: What We Already Knowmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, involving the scientific community in the instrumentation process ensures intensive use of the collected data (see, e.g. Bertogg & Szydlik, 2016;Gauthier & Gianettoni, 2013;Keller, 2013 for the use of items and scales proposed on the basis of calls for instruments).…”
Section: Call For Instrumentsmentioning
confidence: 99%
“…A second approach, related to the first one, comes from the research on inter-generational family relationships across households, which focuses on the various forms of practical or emotional support that is exchanged between family members, particularly between adult children and their aged parents (e.g. Bertogg and Szydlik 2016). A third approach lies in the life course perspective, in which family is studied in terms of family-related transitions and biographical phases (Ammar et al 2014;Elder 1977).…”
Section: Introduction To the Topicmentioning
confidence: 99%